Germination of Senna Occidentalis link: seed at different osmotic potential levels - Delachiave, Maria Elena Aparecida [UNESP]; Pinho, Sheila Zambello De [UNESP] (Instituto de Tecnologia do Paraná - Tecpar, 2003)
The objective of this research was to study the effect of osmotic potential and salinity on the germination of seeds of Senna occidentalis, with and without a change of solutions. The percentage and rates of germination decreased according to decrease of potential, being more drastic when the substitutions of solutions were not made. The largest reductions were observed with the PEG solutions, with and without substitutions.

O objetivo da pesquisa foi estudar o efeito de potenciais osmóticos e salinidade na germinação de sementes de Senna occidentalis, com e sem troca da solução. A porcentagem e a velocidade de germinação diminuíram com o decréscimo do potencial, sendo mais drástica quando as soluções não foram trocadas. As maiores reduções foram observadas nas soluções com PEG, com e sem troca da solução.
Keywords: Germination; seed; osmotic potential; Senna occidentalis